Exploration of personality in the patients with the inflammatory bowel disease - Trikoš, Lela; Jojić, Njegica; Knežević, Goran; Živanović, Marko; Svorcan, Petar; Jovanović, Aleksandar (Vojnosanitetski pregled, 2021)
Abstract Background/Aim. Inflammatory bowel diseases (IBD), which include the ulcerative colitis (UC) and the Crohn’s disease (CD), are chronic diseases, the course of which is under the influence of numerous psychosocial factors. The aim of this study was the exploration of the personality traits of patients with IBD. Methods. This cross-sectional study has been conducted at the University Clinical Hospital Centre Zvezdara, Belgrade, Serbia. The study involved 150 patients suffering from IBD of both genders, out of which 50.7% and 49.3% of the patients suffering from UC and CD, respectively. The main inclusion criteria were: age 18 to 65 years and confirmed the diagnosis of UC or CD in remission. The sociodemographic and disease related data were collected from the hospital medical records. The personality traits related data were collected using the self-report forms of The Revised NEO Personality Inventory (NEO PI–R) and the inventory for the Assessment of Dysregulation (DELTA 10). Results. At the domain-level, the significant differences between IBD sample and normative sample were found in the Neuroticism (p < 0.01) and the Disintegration (p < 0.01). At the facet-level, the IBD sample scored significantly higher than the normative sample on Anxiety (p < 0.01), Assertiveness (p < 0.01), Tender-Mindedness (p < 0.01) and Dutifulness (p < 0.01), and the significantly lower scores on Warmth (p < 0.01), Excitement Seeking (p < 0.01), Positive Emotion (p < 0.01), Actions (p < 0.01), and on the all facets of Disintegration except Depression, Somatoform Dysregulation and Social Anhedonia (p < 0.01). The differences between UC and CD were found only at the facet-level. The facets that adds the most predictive power to the discriminative function is the General Executive Impairment, followed by Warmth, Self-Discipline, Depression and Mania. Conclusion. The IBD patients showed to differ from the general population in terms of basic personality structure at the domain-level, and at the facet-level. The differences between the UC and CD patients can be found only at the facet-level. Screening of the personality traits and early detection of the IBD patients who are at a greater risk of mental disorders and bad psychosocial functioning can enable their adequate prevention and improve the course of the disease.